Blood Pressure and Risks of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of 209 Prospective Studies. Issue 1 (July 2020) - Ou, Ya-Nan; Tan, Chen-Chen; Shen, Xue-Ning; Xu, Wei; Hou, Xiao-He; Dong, Qiang; Tan, Lan; Yu, Jin-Tai
Abstract : Controversies persist regarding the association between blood pressure (BP) and the risks of cognitive impairment and dementia due to inconsistent definitions of BP exposure and varying population characteristics. Here, we searched PubMed and performed a meta-analysis of the influence of BP exposure on the risks of cognitive disorders in prospective studies. Dose-response analyses were performed to illustrate the existence of linear/nonlinear relationships. The credibility of each meta-analysis was evaluated according to the risk of bias, inconsistency, and imprecision. Of the 31 628 citations, 209 were included in our systematic review, among which 136 were eligible for the meta-analysis. Overall, stronger associations were found in midlife than late-life. Moderate-quality evidence indicated that midlife hypertension was related to a 1.19- to 1.55-fold excess risk of cognitive disorders. Dose-response analyses of 5 studies indicated that midlife systolic BP >130 mm Hg was associated with an increased risk of cognitive disorders. With regard to BP exposure in late-life, high systolic BP, low diastolic BP, excessive BP variability, and orthostatic hypotension were all associated with an increased dementia risk. Encouragingly, the use of antihypertensive medications exhibited a 21% reduction in dementia risk. The U-shaped dose-response curve indicated that the protective window of diastolic BP level was between 90 and 100 mm Hg for low risk of Alzheimer disease. The relationships between BP variables and cognitive disorders are age- and BP type-dependent. Antihypertensive medications were associated with a reduced risk of dementia. However, the optimal dose, duration, and type for preventing cognitive disorders warrant further investigation. Abstract : Supplemental Digital Content is available in the text.